Polish Banking System after the World War II (Part II) - Sura, R.; Cура, Р. (Східноєвропейський національний університет імені Лесі Українки, 2016)
The banking model in Poland and regulations on this matter have been subject to profound changes after World War II and aimed at «ideologisation» of theseareas. In fact, all the positive trends initiated before 1939 have been reversed to the negative side. Process of renaming and nationalizing of banks started, while keeping their total subordination to the state and party apparatus. Partly new institutions such as the Narodowy Bank Polski were created or pre-war institution as the Bank Gospodarstwa Krajowego was reactivated. The Narodowy Bank Polski was exempt from all state and local taxes. All the evidence issued by the bank was free from stamp duties, banking books and other writings, included in the accounting and extracts thereof certified by the bank, had probative value of public documents. On the other hand, what is especially important documents stating the obligations of the bank statement, that based on this claim is enforceable and legally mature for execution, had the power to writs of execution. Executors’ clause to these titles was given by the appropriate town court according to the provisions of the Code of Civil Procedure. У повоєнний час польський Національний банк, який був ефективним інструментом в руках правлячої комуністичної партії, займав привілейоване становище порівняно із іншими державними банками. У комуністичні часи привілейоване становище банків, установ, націоналізованих державою і повністю їй підпорядкованих як частини державного апарату, було зрозуміле з точки зору панівної тоді філософії права і принципів правлячої партії. На тлі політичних реформ після 1989 року баланс у банківській системі не був відновлений, що оціненюється нами негативно. Таке збереження привілеїв Польського національного банку в демократичній державі після1989 року було цілком незрозумілим, адже принцип рівності перед законом був проголошений як один з основоположних. Підтримка з боку держави Польського національного банку у такій мірі після 1989 року є безпрецедентним явищем у Європейському Союзі. Таке неконкурентне становище пояснюється впливом сильного банківського лоббі на законодавчу діяльність у Польщі.
Польська банківська система після Другої світової війни (частина II)
Keywords: Polish banking system; Polish banks; banking law; банківська система; банки; банківське право; Польща